ULTRASTRUCTURAL ORGANIZATION FEATURES OF PERIODONTAL TISSUES AFTER TWELVE WEEKS OF OPIOID INFLUENCE - Fik, V.B.; Paltov, Ye.V.; Kryvko, Yu.Ya. (World of Medicine and Biology, 2020)
In the experiment on white rats, ultrastructural studies of periodontal tissues were carried out against the background of twelve-weeks opioid action. Animals were subjected to intramuscular injections of an opioid analgesic with a gradual increase in the mean single dose every two weeks. The initial dose was 0.212 mg/kg, and within 11–12 weeks the dose was increased up to 0.3 mg/kg. The results of submicroscopic studies have revealed the progression of chronic sclerosing inflammation in the periodontium and the development of regenerative-plastic deficiency of epitheliocytes, endothelial cells and the periodontium structural components, which was caused by a long-term opioid action.
Keywords: periodontium; rat; opioid; ultrastructure